PENTINGNYA PENDIDIKAN AGAMA ISLAM SEJAK DINI GUNA MEMINIMALISIR KENAKALAN REMAJA - Aulia Afriani Lestari; Try Susanti; Aunia Afriani Lestari; Raihan Delpha Amir; Wahyudin (STKIP Subang, 2025)
This paper deals with the learning of islamic relegious education from and early age juvenile delinquency in many types, as well as the antecedent factors. Severalfactors causing the behaviors are deserving parents’ attention (due to broken home), influence of peer friends, laziness, and being uncomfortable with teacher presence. The school deals with the problems mainly in three ways: preventive, repressive, and curative. Could be the lack of an islamic school based containeror fasility such as the Madrasah Diniyah.